Optimization of Logistics Management In Health Services: Literature Review - Salsabila, Annisya; Kusuma, Putri Naira; Lesmana, Aurelia Editha; Iswanto, Acim Heri; Istanti, Novita Dwi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Logistics management in healthcare plays an important role in improving operational efficiency and the quality of patient service. This article discusses strategies for optimizing logistics management, such as the use of health information technology, innovations in logistics systems, and procurement with umbrella contract methods. The aim of this research is to explore how logistics management can improve the efficiency and effectiveness of health care. The research method used is the study of literature to analyze various strategies for optimizing logistical management in health care. The research uses the method of systematic review by studying five elective articles within the period of publication of the last five years. Research results show that optimizing logistics management can help improve the quality of health care and patient satisfaction. Despite this, there are still challenges, such as the problem of the storage of goods, fluctuating needs for medical equipment, and problems in human resource management. Efforts are needed to address these challenges so that logistics management can be optimized in support of effective health care. In conclusion, good logistical management in healthcare can bring great benefits in terms of improving operational efficiency, reducing costs, and improving the quality of patient service.